Assessment on awareness of rational prescribing practices among medical interns in a tertiary care hospital: a questionnaire based study - R., Manasa C.; L., Kalpana; M., Veena R.; H., Lavanya S.; D., Bharath Kumar V. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Awareness about rational use of Medicines is required to improve the quality of health care system. Attitude towards rational drug use is also an utmost importance as they constitute the future generation doctors. Methods: A set of 13 questionnaire is given to the interns through an online link to their e-mail which contains informed consent and questionnaires. Respondents has to select the best suitable option and after which the data will be compiled and statistically analyzed. Results: Age of the study participants range from 22-26yrs. Half of them have finished major postings. Almost 96.1 % of them were aware of the term essential drugs. Only 25% of them said that they have NLEMI at work place, 75% of them were aware of the term Rational use of Medicines. Only 32% of them were aware of the term P drugs. 44% of them were aware of STEP criteria for selection of drug and 47% of them were aware of the updated prescribing format. 8% knew the difference between old and new prescription format, 25% of them always prescribe. Almost 82% of them narrate regarding the disease and drug therapy, 31% of them prescribe only generic name. Conclusions: Educational intervention like CME and practical hands on training in Rational use of Medicines would help them in better understanding of the subject and its clinical implications thereby decreasing the prescribing errors.